Mass spectrometry combined with affinity probes for the identification of CP4 EPSPS in genetically modified soybeans. (18th June 2019) - Devi, Shobha; Chu, Pei‐Yu; Wu, Bo‐Hung; Ho, Yen‐Peng
Abstract: Sample preparation methods used for genetically modified organisms (GMOs) analysis are often time consuming, require extensive manual manipulation, and result in limited amounts of purified protein, which may complicate the detection of low‐abundance GM protein. A robust sample pretreatment method prior to mass spectrometry (MS) detection of the transgenic protein (5‐enolpyruvylshikimate‐3‐phosphate synthase [CP4 EPSPS]) present in Roundup Ready soya is investigated. Liquid chromatography‐multiple reaction monitoring tandem MS (nano LC‐MS/MS‐MRM) was used for the detection and quantification of CP4 EPSPS. Gold nanoparticles (AuNPs) and concanavalin A (Con A)‐immobilized Sepharose 4B were used as selective probes for the separation of the major storage proteins in soybeans. AuNPs that enable the capture of cysteine‐containing proteins were used to reduce the complexity of the crude extract of GM soya. Con A‐sepharose was used for the affinity capture of β‐conglycinin and other glycoproteins of soya prior to enzymatic digestion. The methods enabled the detection of unique peptides of CP4 EPSPS at a level as low as 0.5% of GM soya in MRM mode. Stable‐isotope dimethyl labeling was further applied to the quantification of GM soya. Both probes exhibited high selectivity and efficiency for the affinity capture of storage proteins, leading to the quantitative detection at 0.5% GM soya, which is a level below the current European Union's threshold for food labeling. The square correlation coefficients were greater than 0.99. The approach for sample preparation is very simple without the need for time‐consuming protein prefractionation or separation procedures and thus presents a significant improvement over existing methods for the analysis of the GM soya protein.